Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3802/jgo.2016.27.e28
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes mellitus on oncological outcomes after radical hysterectomy for early stage cervical cancer

Abstract: ObjectiveTo evaluate the relationship between type 2 diabetes mellitus (DM) and oncological outcomes in early stage cervical cancer patients who underwent radical surgical resection.MethodsPatients with early stage cervical cancer diagnosed between 2001 and 2014 were retrospectively enrolled. We assessed the outcomes of 402 non-DM and 42 DM patients with cervical cancer. We tested the prognostic value of DM via Cox proportional hazard modeling.ResultsPatients with DM were more likely to be older and overweight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Early stage CC patients with type 2 DM have a poorer oncological outcome than patients without DM [95]. These concepts are summarized in Figure 3.…”
Section: T2d and Cervical Cancer (Cc)mentioning
confidence: 99%
“…Early stage CC patients with type 2 DM have a poorer oncological outcome than patients without DM [95]. These concepts are summarized in Figure 3.…”
Section: T2d and Cervical Cancer (Cc)mentioning
confidence: 99%
“…[ 12 16 ] Considering the prognostic roles of diabetes, numerous studies also have investigated its predictive role in cervical cancer prognosis. [ 17 26 ] Some studies reported that diabetes was associated with poor survival in cervical cancer patients, [ 17 , 24 , 25 ] but others indicated that diabetes had no significant influence on the prognosis of cervical cancer. [ 20 , 27 ] Therefore, the role of diabetes in predicting the prognosis of cervical cancer is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies that have shown that type 2 diabetes resulted in poor oncological outcomes in patients with early stage cervical cancer. 36,37 These proposed associations were not reflected in this study, which could be the result of both low overall prevalence of NCD comorbidity in the study population and a small number of patients undergoing or completing chemoradiation.…”
Section: Clinical Factorsmentioning
confidence: 60%